Exploring the structural and photophysical properties of tri-cation mixed halide double perovskites (Cs2AgIn0.85-XCeXBi0.15Cl6) for high-performance phosphor-based WLEDs - Ravi, Nalini; Kanapathi, Prakash; Mohan, Subramaniam; Appadurai, Tamilselvan (Dalton Transactions, 2025)
Owing to their superior optoelectronic properties, lead-free halide double perovskites (HDPs) have been extensively studied for a wide range of optoelectronic applications, especially for fabricating white light-emitting diodes (WLEDs). Considering white light emission, the HDP structure's dual octahedral configuration facilitates greater lattice distortion, thereby fostering strong electron-phonon coupling-derived self-trapped exciton (STE) emission upon photoexcitation. Herein, we propose facile fabrication of a highly feasible phosphor-converted white light LED and an intensive analysis of the structural, compositional and photophysical properties of a tri-cation mixed halide double perovskite. We chose Cs2AgIn0.85Bi0.15Cl6 as a potential candidate for electroluminescent-based white light LED devices as its composition exhibits high stability, direct-allowed transition, and a notable photoluminescence quantum yield. However, we incorporated a lanthanide ion (Ce3+) into this cubic HDP structure via tri-cation mixing at the B `' site (Cs2AgIn0.85-XCeXBi0.15Cl6) to internally disturb structural periodicity and further enhance STE emission. Initially, powder XRD revealed the lattice expansion induced by Ce3+ incorporation, while XPS and TEM verified the substitution of Ce3+ at the In3+ site. Meanwhile, compositional and optical studies established the role of Ce3+ in retaining the direct allowed transition by effectively replacing the In3+ site. Urbach energy (EU), a measure of energetic disorderness at band edges, was found to be significantly reduced, showing a value of 135 meV for the Ce-5% sample. Most significantly, PL emission studies revealed an appreciable enhancement in the PL intensity with a prolonged STE lifetime of 670 ns for Cs2AgIn0.80Ce0.05Bi0.15Cl6, indicating improved radiative recombination. Besides, excitation-dependent Pl and PLE studies revealed that the emission solely came from the STE states. Elaboratively, vibrational studies elucidated that the Ce-5% sample exhibited a restabilized elpasolite structure and enhanced lattice phonons, which ultimately helped in boosting STE emission, as proven by the Huang-Rhys factor (S = 13). Finally, an efficient and durable phosphor-converted WLED was fabricated, and its performance was assessed, revealing CIE coordinates of (0.35,0.32), a CCT of 4368 K, and an extremely high CRI (Ra) of 92. Thus, our work provides an exclusive strategy to enhance the STE emission for potential application in electroluminescent-based WLED devices.